Youth ice hockey COVID-19 protocols and prevention of sport-related transmission - Krug, A.; Appleby, R.; Pizzini, R.; Høeg, T. B. (British Journal of Sports Medicine, 2022)
Objectives This observational study evaluated the impact of return-to-play protocols to prevent transmission of SARS-CoV-2 in a youth ice hockey programme in Virginia Beach, Virginia. Methods Following an outbreak of SARS-CoV-2 in November 2020, a COVID-19 Response Team evaluated the epidemiological data to identify transmission dynamics and develop enhanced protocols to prevent transmission. During the subsequent 18-week study period, incident cases were investigated to identify the likely transmission source; testing, quarantine and isolation recommendations were provided to families in accordance with Centers for Disease Control and Prevention guidelines. Results Simple but stringent protocols were implemented among 148 youth ice hockey players ages 6-18. Players were required to arrive at the rink in full gear; locker rooms were closed, building entry was limited to one parent per player, and masks were required at all times except for players on the ice. Following implementation of the enhanced protocols, more than 500 practices and games were completed with at least 15 858 athlete-hours of exposure and no within-programme COVID-19 transmission was detected despite high community incidence and sporadic household exposures. Conclusion This study suggests indoor youth sports can operate safely with appropriate protocols in place, even within communities of high COVID-19 transmission, even when athletes are not yet vaccinated or wearing masks during play. Transmission appears to be more likely in congested indoor areas involving adults than on the ice during play. Protocols should be developed in collaboration with programme participants. Strong collaboration in the interest of youth sports can motivate adoption of protocols which prevent within-team transmission.